FRACTIONATION OF CARBON ISOTOPES IN BIOSYNTHESIS OF FATTY ACIDS BY A PIEZOPHILIC BACTERIUM MORITELLA JAPONICA STRAIN DSK1 - Fang J.; Uhle M.; Billmark K.; Bartlett D.H.; Kato C. (My University, 2006)
We examined stable carbon isotope fractionation in biosynthesis of fatty acids of a piezophilic bacterium Moritella japonica strain DSK1. The bacterium was grown to stationary phase at pressures of 0.1, 10, 20, and 50 MPa in media prepared using sterile-filtered natural seawater supplied with glucose as the sole carbon source. Strain DSK1 synthesized typical bacterial fatty acids (C14-19 saturated, monounsaturated, and cyclopropane fatty acids) as well as long-chain polyunsaturated fatty acids (PUFA) (20:6?3). Bacterial cell biomass and individual fatty acids exhibited consistent pressure-dependent carbon isotope fractionations relative to glucose. The observed ??FA-glucose (-1.0? to - 11.9?) at 0.1 MPa was comparable to or slightly higher than fractionations reported in surface bacteria. However, bulk biomass and fatty acids became more depleted in 13C with pressure. Average carbon isotope fractionation (??FA-glucose) at high pressures was much higher than that for surface bacteria: -15.7?, -15.3?, and -18.3? at 10, 20, and 50 MPa, respectively. PUFA were more 13C depleted than saturated and monounsaturated fatty acids at all pressures. The observed isotope effects may be ascribed to the kinetics of enzymatic reactions that are affected by hydrostatic pressure and to biosynthetic pathways that are different for short-chain and long-chain fatty acids. A simple quantitative calculation suggests that in situ piezophilic bacterial contribution of polyunsaturated fatty acids to marine sediments is nearly two orders of magnitude higher than that of marine phytoplankton and that the carbon isotope imprint of piezophilic bacteria can override that of surface phytoplankton. Our results have important implications for marine biogeochemistry. Depleted fatty acids reported in marine sediments and the water column may be derived simply from piezophilic bacteria resynthesis of organic matter, not from bacterial utilization of a 13C-depleted carbon source (i.e., methane). The interpretation of carbon isotope signatures of marine lipids must be based on principles derived from piezophilic bacteria. ? 2005 Elsevier Inc. All rights reserved.
Keywords: CARBON ISOTOPE; GEOMICROBIOLOGY; ISOTOPIC FRACTIONATION; BACTERIA (MICROORGANISMS); MORITELLA JAPONICA